The image of the ruler of Moldova Petru Rares in contemporary foreign sources - Niemczyk, Katarzyna (Balcanica Posnaniensia. Acta et studia, 2020)
The aim of the paper is to refer how the ruler of Moldova – Petru Rareş was described in the contemporary sources, so that we can find the answer for the question how Petru Rares was perceived by the rulers from Europa and Ottoman Empire. There were analyzed various sources that showed the standpoint of the Polish king Sigismund I, sultan Suleyman the Great, Ferdinand Habsburg towards Rareş. Thanks to this analysis it can be said that the rulers from Europa and Ottoman Empire perceived Rareş as a man who was disloyal, unfaithful and they definitely didn’t trust him. This opinion had huge influence on the final defeat of Rareş.